SKOR APGAR RENDAH SEBAGAI FAKTOR RISIKO UNTUK PALSI SEREBRAL PADA ANAK - , Agung Supriyanto; , Prof. dr. Djauhar Ismail, MPH, Ph.D, Sp.AK. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background. There are many risk factors of cerebral palsy including prenatal, perinatal, and postnatal period. Low Apgar score (0-3) at 5 minutes is considered as a risk factor of cerebral palsy in children. Objectives. To determine the low Apgar score as a risk factor of cerebral palsy in children. Methods. This was a case-control study. Subjects were children admitted in Dr. Sardjito General Hospital Yogyakarta from January 2005 to Mei 2011. Matching was applied to case and control by age and gender. Data from 38 cases and 38 controls were analyzed. Results. The possible risk factors contributed to cerebral palsy in children were low Apgar score OR = 12.9 (95% CI : 3.39-49.50), gestational age < 37 weeks OR = 67.5 (95% CI : 13.31-342.27) and birth weight < 2500 grams OR = 37.6 (95% CI : 9.30-151.87). Sixty percents of cases had those possible risk factors. Conclusion. The low Apgar score is the risk factor of cerebral palsy.